Bringing down the moon - Emmett, Jonathan; Cabban, Vanessa (Walker London, 2002)
When Mole burrows out of the ground one night and catches sight of the moon, he thinks it is the most beautiful thing he's ever seen and he wants it, so he sets about trying to pull it down - to no avail. Then he notices it's in a puddle, but when he picks it up it breaks!